To scroll or not to scroll: Examining social media as a mediator for attachment security and internal stress - Langlais, Michael; Shufford, Kevin; Citrano, Emily; Lau, Kevin; Randall, Ashley (American Journal of Social Sciences and Humanities, 2023)
Because attachment insecurity is associated with higher reports of social media (SM) use, and SM use has been shown to reduce the quality of interpersonal interactions, it is possible that SM use may mediate the association between attachment insecurity and experiences of internal stress (i.e., stress within a relationship). The present study uses daily diary data from 154 participants currently in a romantic relationship. Both concurrent (same day) and lagged (next day) effects were examined. Attachment anxiety was positively associated with experiences of internal stress on day 2 (concurrent effect) and day 3 (lagged effect). Partial support was found for associations with attachment avoidance; those reporting higher attachment avoidance reported higher internal stress on day 3 (lagged effect), but not on day 2 (concurrent effect). SM use did not mediate the association between insecure attachment and internal stress, as hypothesized. Implications and future directions are presented.